1999
DOI: 10.1152/ajpendo.1999.276.3.e503
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of protein kinase C to ET-1-induced proliferation in human myometrial cells

Abstract: The role of protein kinase C (PKC) in endothelin-1 (ET-1)-induced proliferation of human myometrial cells was investigated. ET-1 dose dependently stimulated DNA synthesis and the number of cultured myometrial cells. Inhibition of PKC by calphostin C or Ro-31-8220 or downregulation of PKC eliminated the proliferative effects of ET-1. The failure of two protein tyrosine kinase (PTK) inhibitors (tyrphostin 51 and tyrphostin 23) to affect ET-1-induced proliferation supports the hypothesis of noninvolvement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Although this interpretation of our data is attractive, there is no information on leiomyoma through which to address this issue. The translocation of PKCÂ following ET-1 treatment is consistent with our previous findings in which this isoform has emerged as critical for mitogenic signal transduction in human myometrial cells [6]. The functional significance of PKCÂ has not yet been identified in a tumor originating in uterine smooth muscle, but experiments on HEC1-B cells, a human endometrial adenocarcinoma cell line, have shown a selective redistribution of PKCÂ in response to a phorbol ester [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although this interpretation of our data is attractive, there is no information on leiomyoma through which to address this issue. The translocation of PKCÂ following ET-1 treatment is consistent with our previous findings in which this isoform has emerged as critical for mitogenic signal transduction in human myometrial cells [6]. The functional significance of PKCÂ has not yet been identified in a tumor originating in uterine smooth muscle, but experiments on HEC1-B cells, a human endometrial adenocarcinoma cell line, have shown a selective redistribution of PKCÂ in response to a phorbol ester [20].…”
Section: Discussionsupporting
confidence: 90%
“…That endothelin-1 (ET-1) might be a new regulator of the growth of uterine tumors is supported by the presence of functional ET A receptors (ET-1 selective) in leiomyoma [2][3][4]. Only these ET A receptors are involved in the mitogenic effect of ET-1 in cultured human myometrial cells [5] and substantial evidence indicates that the protein kinase C (PKC)-signaling pathway is required for ET-1-induced myometrial cell growth [6]. The demonstration that PKC may regulate this proliferative effect makes reasonable the hypothesis that the enzyme is a pivotal regulator of uterine cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in bovine tracheal smooth muscle cells ET-1-induced DNA synthesis and ERK 1/2 activation are inhibited by pretreatment with PTX or following PKC downregulation [21]. ET-1-induced DNA synthesis is also inhibited in myometrial cells and immortalized Rat-1 fibroblasts following PKC downregulation [17,39,40]. On the other hand, PTX has no effect on ET-1 induced, ETA receptor-dependent DNA synthesis in renal mesangial cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were carried out at as previously described with cultured human myometrial cells (14). Subconfluent leiomyoma cells were left untreated or treated with 0.1 mmol/l PDB for 48 h in serum-free medium and subsequently washed twice with PBS.…”
Section: Western Blot Analysis Of Pkcmentioning
confidence: 99%
“…Conventionally, calcium, protein kinase C (PKC) and protein tyrosine kinase (PTK) signaling pathways are thought to contribute to ET-1-induced cell growth and differentiation. However, in normal human myometrial cells, substantial evidence indicates that only the activation of PKC is required for ET-1-induced proliferation (14). PKCs constitute an expanding multigene family, so far with 12 known isoforms classified into three subfamilies on the basis of their structure and ability to bind cofactors.…”
Section: Introductionmentioning
confidence: 99%